EMPLOYEE RELATION AND PRACTICES AT MANUFACTURING ORGANIZATION – SPECIAL REFERENCE TO ODISHA - Nayak, Sasmita (International Journal of Psychosocial Rehabilitation, 2020)
In current years the importance of human resource has been increasing the most. The concept of dealing human resource is known as employee relation. All the physical resources have been used and handle by employee of the organization like that all type of creativity and innovation are only done by employees of the organisation. This is simply possible when employees are in healthy mind with positive relationship among the employees, which help employees as well as organizational growth. Any organization with a decent employee relations program delivers fair and consistent dealing to all employees, so they will be committed to their works and loyal to the organization. Employees loyalty, commitment, dedication are key factor for organisational growth and success. It is only possible when there is healthy employee relation persist in the organization. Every organisation should give emphasise on employee relationship practice within the organisation by working on the concept like good communication practice, appreciation for the work completed and for every small achievement, good work-life balance, good relationships with superiors, learning and career development, Job security, attractive fixed salary etc. Subsequently the evolutions of contemporary employee relation management, encouraged employees and employee’s turnover in an organization have been the essential issues for HR department. HR department needs to motivated employees, adopt different employee relation practices and desire to retain experienced employees to find real time solutions. Organizations implements Employee Relation practices to shining expertise of its employees which eventually contribute to better organizational performance The aim of this paper is to study the employee relations and also to identify various employee relations practices used by manufacturing organisation in Odisha. The study adopted a cross-sectional survey research design and used a stratified random sampling technique from selected manufacturing organizations in Odisha. Data was collected using structured questionnaires and analyzed using descriptive statistics and the results presented using tables.